Information Security : 16th International Conference, ISC 2013, Dallas, Texas, November 13-15, 2013, Proceedings - Desmedt, Yvo.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 16th International Conference on Information Security, ISC 2013, held in Dallas, Texas, in November 2013. The 16 revised full papers presented together with 14 short papers were carefully reviewed and selected from 70 submissions. The papers cover a wide range of topics in the area of cryptography and cryptanalysis and are organized in the following topical sections: security of operating systems; secret sharing; encryption; malware and Critical infrastructures; cryptanalysis; block ciphers and stream ciphers; entity authentication; usability & risk perception; access control; computer security; privacy attacks; cryptography.
Keywords: Software engineering; Logic design; Computer science; Artificial intelligence; Computer Communication Networks; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages; Artificial Intelligence; Computer Communication Networks